ALGUNAS IMPLICACIONES DE LA TECNOLOGÍA PESQUERA EN EL MEDIO NATURAL DE BARRA DEL COLORADO. LIMÓN, COSTA RICA - Villalobos Chacón, Luis (2000)
This study was carried in the community of Barra of colorado, Limón, costa Rica, where diverse conflicts for the use of the marine and coastal resources have been generated in the last years, captured for the local and strange inhabitants. It are emphasised in some aspects of technological character used by the local fishermen and sample how such factors don't constitute, necessarily, the main reason of the growing deterioration from the fishing resources, also influencing other elements of equal or old relevancy.